The Nigeria War of Unity 1967-1970: Strategies and Diplomacy - Oluwaseun Samuel Osadola; Serifat Bolanle Asiyanbi (Polit Journal Scientific Journal of Politics, 2022)
This study examines the aim and strategies of the Nigerian Civil War 1967-1970 and, emphasizes the diplomatic positions and war strategies adopted by the two sides (Federal Government and Biafra secessionist) involved. It agrees that series of researches have been carried out as regards the Nigerian Civil War but only a few viewed it on the ground of diplomatic maneuvering and strategy. The various literatures laid more emphasis on the causes, dimensions and effects of the war without a thorough analogy on the use of tact and strategy in the context of the war. The study also examines the use of propaganda, military tact, media, peace talks and summits in the context of the Nigerian civil war. This study is divided into two parts; the use of strategies by the Nigerian government and the Biafra people, as well as the peace talks and summits that took place during the war. Both primary and secondary sources of data are employed in this research.